On the Importance of Time for GIS View Measures and Their Use in Hedonic Property Models: Does Being Temporally Explicit Matter?. Issue 2 (16th August 2013) - Crawford, Thomas W.; Bin, Okmyung; Kruse, Jamie B.; Landry, Craig E.
Abstract Progress in GIScience has advanced the ability to represent and analyze view characteristics. GIS‐derived view measures requiring digital elevation surface models are used in hedonic property models to quantify the amenity value of view for parcel sales transactions. Ideally models should represent surface elevations that are temporally synchronized with parcel sale dates. Temporal synchronization for studies spanning multiple years may require significant effort. Few studies have undertaken this effort, leading us to investigate in this research the need to be temporally explicit. We evaluate two competing surface model approaches based on: (1) a single year 2000 LiDAR surface product; and (2) annual‐specific surface products for 1995–2002. Two competing view measures based on the different surface approaches are constructed for 561 parcel transactions during 1995–2002 in a coastal North Carolina county and are input into hedonic regression models. Results showed that being temporally explicit did matter in terms of finding significantly different view measures but did not matter in terms of finding significantly different effects of view on parcel sales prices. Despite mixed results for our case study, we advise that future research involving GIS‐based view measurement should consider the spatial and temporal contexts of study area development patterns when evaluating the need to be temporally explicit.